A Comparison of Bipolar Electrocautery and Chemical Cautery for Control of Pediatric Recurrent Anterior Epistaxis. (30th June 2015) - Johnson, Nathan; Faria, John; Behar, Philomena
Abstract : Objective: To compare the outcome of children with anterior epistaxis treated intraoperatively with either bipolar electrocautery or silver nitrate chemical cautery. Study Design: Case series with chart review. Setting: Tertiary‐care pediatric otolaryngology practice. Subjects: Children aged 2 to 18 years treated with either intraoperative bipolar electrocautery or silver nitrate chemical cautery of the anterior nasal septum for recurrent anterior epistaxis. Methods: Any reported bleeding event after surgery was recorded. The mean time from surgery to recurrent epistaxis was compared between groups. Results: Fifty patients underwent bipolar electrocautery, while 60 patients underwent silver nitrate chemical cautery. Within 2 years, 1 (2%) patient in the bipolar electrocautery group and 13 (22%) patients in the silver nitrate chemical cautery group had recurrent epistaxis ( P =. 003). Two years after treatment, there was no difference between treatment groups. Overall, 4 patients (8%) had recurrent epistaxis postoperatively in the bipolar electrocautery group at a mean of 4.34 years after treatment, while 17 (28.3%) patients recurred after a mean of 1.53 years of treatment in the silver nitrate chemical cautery group ( P =. 01). Conclusion: Compared to those treated with chemical cautery, those treated with bipolar electrocautery had a longer nosebleed‐free period and a lower incidence of recurrent epistaxis within 2 years of treatment. Beyond 2 years, the treatment methods are equivocal. Bipolar electrocautery may be a superior treatment in children who will not tolerate in‐office chemical cautery, in those with a risk of severe bleeding, or when it can be combined with other operative procedures.